Testicular origin of epigenetic inheritance independent of sperm mitochondrial DNA and epididymal exposure - Zhuqing Wang; Yasuhiro Yamauchi; Sheng Chen; Huili Zheng; Monika A. Ward; Wei Yan (Proceedings of the National Academy of Sciences, 2026)
Paternal epigenetic inheritance remains mechanistically unresolved. Recent studies propose that environmental exposures induce mitochondrial DNA (mtDNA)-dependent transcription in sperm during epididymal transit, altering small RNA content and offspring phenotypes. Here, we show that mature murine sperm are effectively devoid of mtDNA, precluding mtDNA-dependent transcription, and that sperm-borne mitochondrial RNAs originate during spermatogenesis. Testicular sperm transmitted diet-induced metabolic traits as efficiently as, and in most cohorts more efficiently than, epididymal sperm. These findings establish testicular inheritance independent of sperm mtDNA transcription and epididymal exposure.